Radio Broadcasting and the Adaptation of Folk Media in Cultural Promotion at Select Stations of North Central, Nigeria - Adekaa, Bridget Sewuese; Igyuve, Anthony; Akase, Ter Moses (Journal of Communication, 2024)
Purpose: This study aims to explore the utilization of folk media in Nigeria for radio broadcasting and cultural advocacy, focusing on preserving and advancing cultural heritage in Northcentral Nigeria. Methodology: Employing the Uses and Gratification Theory as a framework, the research utilized a mixed-method approach to gather data. Findings: The findings of the study highlight the importance of enhancing strategies to capture and sustain listener interest in folk media programmes. Incorporating interactive elements, storytelling techniques, or other methods to improve audience engagement is recommended to increase audience interest. Unique contribution to theory, policy and practice: The study suggests that with the advancement of technology and the popularity of radio broadcasting, there is a need to explore the adaptation of folk media to this medium. This adaptation could ensure the longevity of folk media and reach wider audiences. Additionally, the study underscores the significance of utilizing folk media for cultural advocacy and recommends efforts to enhance strategies for promoting and preserving cultural heritage through radio broadcasting.